(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the Bureaucratic Ethics in Public Services at the Duampanua Sub-District Office, Pinrang Regency. This research uses qualitative research with case study type. Data collection techniques used observation, interviews and documentation. Research informants amounted to 12 people. Validation of data through triangulation of sources, techniques and time, then analyzed through data reduction, data presentation and drawing conclusions. The results showed that the Bureaucratic Ethics that existed or was applied by the sub-district office were not in accordance with 1) Standardization and formalization, namely there were still many employees who did not follow the SOP. 2) Division of work and specialization, namely the placement of employees is not in accordance with their abilities. 3) Hierarchy of authority, namely the absence of written sanctions related to violations. 4) professionalization, ie there are no specific criteria for position placement. 5) Written documents, namely the filing system still needs improvement.